OPTIMASI PENILAIAN PADA E-LEARNING UNIVERSITAS MADURA DENGAN MENGGUNAKAN METODE SCAFFOLDING - Fauzan Prasetyo Eka Putra; Moh Nazir; Yasir Zain (Jurnal Informatika, 2020)
Delivery of learning material in courses that are efficient in lectures at the University Madura, especially in the Faculty of Engineering and the Faculty of Science Teaching and Education is a difficult thing to do achieved, to be able to provide a good understanding and efficient in learning both mastery and understanding concepts, theories, methods or philosophy of a particular field of science obtained through in-process reasoning student learning and work experience. Some research has attempted to propose a solution in the delivery of learning, but very difficult to find a good method to use. In this research proposed a media optimization method learning by using scaffolding in the application e-learning students in understanding the definition of material lectures, which is by using the method scaffolding will provide increased capabilities students in understanding the learning material, 6 strategies the scaffolding used in e-learning includes: modeling, instructing, explaining, questioning and hints, contingency management, and feeding back. Through e-learning system optimization planning, test results system conducted on 50 respondents for maleand female students produced a percentage of 63.82% for female students and 81.47% for male students as benefit values on the evaluation of e-learning system optimization planning.